2019
DOI: 10.3389/fimmu.2019.02210
|View full text |Cite
|
Sign up to set email alerts
|

mir-124-5p Regulates Phagocytosis of Human Macrophages by Targeting the Actin Cytoskeleton via the ARP2/3 Complex

Abstract: Phagocytosis is a cellular process crucial for recognition and removal of apoptotic cells and foreign particles, subsequently initiating appropriate immune responses. The process of phagocytosis is highly complex and involves major rearrangements of the cytoskeleton. Due to its complexity and importance for tissue homoeostasis and immune responses, it is tightly regulated. Over the last decade, microRNAs (miRNAs) have emerged as important regulators of biological pathways including the immune response by fine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Additionally, recent work found that DHA decreases microglia phagocytic activity of myelin debris in the spinal cord after injury through mir-124 68 , a non-coding nucleotide involved in synaptic plasticity. In macrophages, mir-124 has been shown to regulate actin-related protein 2/3 (ARP2/3), which is involved in the formation of the phagocytic cup 74 . This is in line with results showing that DHA reduced LPS-induced phagocytic activity of microglia, through a reduction of filopodia 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent work found that DHA decreases microglia phagocytic activity of myelin debris in the spinal cord after injury through mir-124 68 , a non-coding nucleotide involved in synaptic plasticity. In macrophages, mir-124 has been shown to regulate actin-related protein 2/3 (ARP2/3), which is involved in the formation of the phagocytic cup 74 . This is in line with results showing that DHA reduced LPS-induced phagocytic activity of microglia, through a reduction of filopodia 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Padilla et al. reported that mir-124-5p regulates phagocytosis of human macrophages by targeting the actin cytoskeleton via the Arp2/3 complex ( 39 ). Silencing of the ARP2/3 complex has also been shown to disturb pancreatic cancer cell migration ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of miRNAs in the regulation of phagocytosis is poorly understood. To date, four miRs have been described as negative regulators of phagocytosis, e.g., miR-24, miR-30b, miR-124-5p and miR-142-3p [ 46 , 47 ]. miR-142-3p directly regulates protein kinase C alpha (PKCα), a key gene involved in phagocytosis.…”
Section: Activation Of Monocytes—the Role Of Mirnamentioning
confidence: 99%
“…miR-124-5p is involved in the regulation of the activity of the actin cytoskeleton. The direct targets of miR-124-5p are ARPC3 and ARPC4 transcripts, which result in reduced expression of the ARP2/3 complex, a crucial regulator of actin polymerization [ 47 ]. miR-21 was described as directly implicated in switching wound-associated macrophages to an anti-inflammatory status after the engulfment of apoptotic cells or efferocytosis [ 28 ].…”
Section: Activation Of Monocytes—the Role Of Mirnamentioning
confidence: 99%